2017
DOI: 10.3732/apps.1600132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of downy mildew resistance gene candidates by positional cloning in maize (Zea mays subsp. mays; Poaceae)

Abstract: Premise of the study:Positional cloning in combination with phenotyping is a general approach to identify disease-resistance gene candidates in plants; however, it requires several time-consuming steps including population or fine mapping. Therefore, in the present study, we suggest a new combined strategy to improve the identification of disease-resistance gene candidates.Methods and Results:Downy mildew (DM)–resistant maize was selected from five cultivars using a spreader row technique. Positional cloning a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Rpv11 , founded on chromosome 5 in a population from Regent, was related to low level of downy mildew resistance in some cultivars of Regent, Chardonnay and Solaris (Schwander et al, 2012 ; Van Heerden et al, 2014 ). Introduced from V. amurensis , dominant Rpv12 was detected in a chromosome 14 of Kozma 20-3 cultivar together with Rpv3-1 (Venuti et al, 2013 ; Kim et al, 2017 ; Possamai et al, 2020 ). Recently, linkage analysis identified three QTLs for P. viticola resistance: Rpv22 on LG 02, Rpv23 on LG15, and Rpv24 on LG18 (Fu et al, 2020 ).…”
Section: Disease Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Rpv11 , founded on chromosome 5 in a population from Regent, was related to low level of downy mildew resistance in some cultivars of Regent, Chardonnay and Solaris (Schwander et al, 2012 ; Van Heerden et al, 2014 ). Introduced from V. amurensis , dominant Rpv12 was detected in a chromosome 14 of Kozma 20-3 cultivar together with Rpv3-1 (Venuti et al, 2013 ; Kim et al, 2017 ; Possamai et al, 2020 ). Recently, linkage analysis identified three QTLs for P. viticola resistance: Rpv22 on LG 02, Rpv23 on LG15, and Rpv24 on LG18 (Fu et al, 2020 ).…”
Section: Disease Managementmentioning
confidence: 99%
“…Single-site fungicides provide both pre- and post-infection protection and include four main chemical classes: phenylamide compounds such as mefenoxam, metalaxyl, and benalaxyl (Magarey et al, 1991 ; Nicholas et al, 1994 ; Falk et al, 1996 ; Underdown et al, 2008 ); strobilurines such as azoxystrobin, trifloxystrobin, famoxadone, and fenamidone (Reuveni, 2001 ; Wong and Wilcox, 2001 ; Genet et al, 2006 ); the carboxylic acid amides like dimethomorph, iprovalicarb, flumorph, benthiavalicarb, mandipropamid (Wicks and Hall, 1990 ; Albert et al, 1991 ; Gisi et al, 2007 ; Reuveni, 2014 ; Nanni et al, 2016 ; Kim et al, 2017 ); and cyano-acetamide-based oxime carbonates like cymoxanil (Gullino et al, 1997 ; Genet and Vincent, 1999 ; Joshi, 2003 ). Both cymoxanil and chlorothalonil are specific, non-systemic, mildew fungicides and are curative if they are applied during the first few days post infection.…”
Section: Disease Managementmentioning
confidence: 99%
“…DM disease was scored in the field using a modified spreader-row technique [2]. Susceptible genotypes (B73 and CML270) were used as two 5-m-long spreader rows with 20 plants per row after every 10th row of the test entries on the border rows of the experimental block ( Figure S1) [44,47]. Seeds of the spreader genotypes germinated after 7 days, then a DM-infected maize plant in a pot was placed in each experimental block for 2 weeks to infect the spreader plants.…”
Section: Evaluation Of the Rils For Dmmentioning
confidence: 99%
“…The PVE diversity in the linkage area was caused by infection pathogenic factor to the response of the resistance maize lines. Based on previous study, Kim et al (2017) and Ruswandi et al (2015) have identified QTL for downy resistance on chromosome 1 using F2 and BC1F2 populations, respectively. Furthermore, it was also reported by Jampatong et al (2013) that QTL related to Pp in the RILs, Lohithaswa et al (2015) found QTL related to Ps (Peronosclerospora sorghi) in F2 population, and QTL linked Ph (Peronosclerospora heteropogoni) character was obtained BC1F2 population (Kim et al 2020).…”
Section: Discussionmentioning
confidence: 99%